Plant LHC-like proteins show robust folding and static non-photochemical quenching - Skotnicová, Petra; Staleva-Musto, Hristina; Kuznetsova, Valentyna; Bína, David; Konert, Minna M; Lu, Shan; Polívka, Tomáš; Sobotka, Roman (Nature communications, 2021)
Life on Earth depends on photosynthesis, the conversion of light energy into chemical energy. Plants collect photons by light harvesting complexes (LHC)-abundant membrane proteins containing chlorophyll and xanthophyll molecules. LHC-like proteins are similar in their amino acid sequence to true LHC antennae, however, they rather serve a photoprotective function. Whether the LHC-like proteins bind pigments has remained unclear. Here, we characterize plant LHC-like proteins (LIL3 and ELIP2) produced in the cyanobacterium Synechocystis sp. PCC 6803 (hereafter Synechocystis). Both proteins were associated with chlorophyll a (Chl) and zeaxanthin and LIL3 was shown to be capable of quenching Chl fluorescence via direct energy transfer from the Chl Qy state to zeaxanthin S1 state. Interestingly, the ability of the ELIP2 protein to quench can be acquired by modifying its N-terminal sequence. By employing Synechocystis carotenoid mutants and site-directed mutagenesis we demonstrate that, although LIL3 does not need pigments for folding, pigments stabilize the LIL3 dimer.
Keywords: proteiny huseníčku; Protein Binding; Synechocystis; Protein Folding; mutace; multimerizace proteinu; xanthofyly; Energy Transfer; zeaxanthiny; Chlorophyll; Chloroplast Proteins; Arabidopsis Proteins; sbalování proteinů; přenos energie; chlorofyl; vazba proteinů; Carotenoids; Mutation; Xanthophylls; proteiny chloroplastové; Zeaxanthins; Protein Multimerization; karotenoidy